Simulation of an ITS Crash Prevention Technology at a No-Passing Zone Site - El Khoury, John (2006)
Crashes at no-passing zones constitute a sizable percentage of the total crashes on two-lane rural roads. A no-passing zone site at a crest vertical curve on route 114 of Southwest Virginia has experienced several traffic crashes that resulted in 12 deaths and 29 injuries over a six-year period. These deaths were the result of head-on collisions caused by illegal passing maneuvers at the no-passing site. A detection and warning system has been devised and implemented at the site with the aim of deterring drivers from illegally conducting a passing maneuver within the no-passing zone area. This system is currently operational and its main function is to warn the no-passing zone violators to abort the illegal maneuver. The authors plan to extend this warning system to the opposing vehicle in the same lane of the persistent violator in order to reduce the crash risk of the illegal passing maneuvers. A new simulation is developed to replicate the outcomes of deploying a warning sign to the opposing driver for crash avoidance purposes. The results indicate that warning the opposing driver would reduce the possible crashes by a mean of 26.3% in the eastbound direction and 33.3% in the westbound direction.